The impact of renal dysfunction after critical illness on the management of cancer - Romano, Thiago Gomes; Chaves, Rodrigo; Alves, Izabela Sinara; Palomba, Henrique (Frontiers in Nephrology, 2025)
A 67-year-old male patient with limited-stage diffuse large B-cell lymphoma was on an R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone) chemotherapy regimen. His Eastern Cooperative Oncology Group (ECOG) Performance Scale score was zero, indicating functional independence for activities of daily living. The patient was admitted to the intensive care unit (ICU) with septic shock in the presence of febrile neutropenia progressing to acute kidney injury, hypoxemic respiratory failure, and systemic arterial hypotension, in addition to the already established hematological dysfunction with thrombocytopenia. During his 32-day ICU stay, he required invasive mechanical ventilation, renal replacement therapy (RRT) and vasopressor drugs, with a focus on control of the infection. The patient was discharged from the ICU with sarcopenia and a serum creatinine level of 2.3 mg/dL, indicating a clearance rate of 24 ml/min/1.73 m2. Oxygen supplementation was needed. What impact did critical illness, more specifically renal dysfunction, have on the planning of onco-hematological treatment in this patient?